Competition between static gear of the small-scale fisheries in Algarve waters (southern Portugal) - ERZINI, K.; GONCALVES, J.M.S.; BENTES, L.; LINO, P.G.; RIBEIRO, J.; MOUTOPOULOS, D.K.; STERGIOU, K.I. (Mediterranean Marine Science, 2010)
Parallel fishing trials with 0.30 mm diameter monofilament gill nets and longlines using small hooks were carried out in the Algarve (southern Portugal) over a one-year period, 1997-1998, with the objective of comparing species composition, catch rates, discards and size ranges. Four hook sizes of ’Mustad’ brand, round bent, flatted sea hooks (numbers 15, 13, 12 and 11) and four mesh sizes of 25, 30, 35 and 40 mm (nominal bar length) of gill nets were used in the trials. Overall, 84 species were caught, with gill nets taking 71 species and longlines 54 species and with 41 species caught by both gears. The amount of discarding was higher for gill nets than for longlines. The catch species composition differed between the two gears, with the commercially valuable sea breams dominating the longline catches whereas small pelagics were relatively more important in the gill nets. Multivariate analysis showed a clear separation between the different sizes of the two gears both in terms of numbers and weights per species. Algarve gill netters and longliners fish the same species assemblage on the same fishing grounds, but have clearly different impacts in terms of catch species composition, catch rates and sizes. This information will be useful for the improved management of these small-scale, multi-species, multi-gear fisheries, where different gears compete for scarce resources. In particular this study provides a basis for a more rational allocation of licenses and control of fishing effort.